Espelho, espelho meu, que professora sou eu?: reflexos e refrações sobre a formação do professor de língua portuguesa e os novos letramentos em um estudo autoetnográfico - Basoni, Isabel Cristina Gomes (2022)
Portuguese language teacher education and New Literacies practices are important topics in the educational field that still need investigation. Thus, this study aims to contribute to the construction of knowledge on such issues. To do so, this research is based on autoethnography as a methodology (ADAMS; JONES; ELLIS, 2015; VERSIANI, 2002; ONO, 2017; PAIVA, 2018; FADINI, 2020; MULIK, 2021)., and presents the researcher’s experiences as its source of data. Those experiences are presented in the light of critical reflections about texts, images, epiphanies, narratives and documents which have been (re)contrstructed in the process of inquiry. Metaphorically speaking, this study engages in a process of looking at oneself in the mirror in which the teacher education process and the teaching practices are reflected, refracted (BAKHTIN/VOLOCHÍNOV, 2014) and interpreted by the teacher researcher, who has in mind her particular role in each moment being presented, each feeling that is revealed, each thought and state of mind that is given away, always in an actively responsible act (BAKHTIN, 2010). This study is based on a post-modern perspective of research and knowledge production which points out to the necessity of unlearning rooted beliefs in the educational field (MOITA LOPES, 2013); making room for the voices of the South (KLEIMAN, 2013); promoting educational practices supported by new ways of thinking and learning, powered by new digital technologies (FERRAZ, 2014; DUBOC, 2011; 2015); and elaborating new proposals for teaching education (FREIRE; LEFFA, 2013; MILLER, 2013; MONTE MÓR, 2013). Based on those principles and on the results obtained in this inquiry, this thesis defends teacher education as a dialogical process in which educational practices are analyzed through critical and reflexive lenses, and experiences as well as knowledge are shared among peers. It also states the importance of understanding educators as subjects who are agents of their educational process, as they engage in practices which aid them to become the “new teacher” who is able to perform with “new subjects” that new literacy research has been pointing out (KALANTZIS; COPE, 2012).